The effects of artificial selection on the maize genome - Wright, S.I.; Bi, I.V.; Schroeder, S.G.; Yamasaki, M.; Doebley, J.F.; McMullen, M.D.; Gaut, B.S. (American Association for the Advancement of Science, 2005)
Domestication promotes rapid phenotypic evolution through artificial selection. We investigated the genetic history by which the wild grass teosinte (Zea mays ssp. parviglumis) was domesticated into modern maize (Z. mays ssp. mays). Analysis of single-nucleotide polymorphisms in 774 genes indicates that 2 to 4% of these genes experienced artificial selection. The remaining genes retain evidence of a population bottleneck associated with domestication. Candidate selected genes with putative function in plant growth are clustered near quantitative trait loci that contribute to phenotypic differences between maize and teosinte. If we assume that our sample of genes is representative, ∼1200 genes throughout the maize genome have been affected by artificial selection.